An Unusual Dermoid Cyst of the Pineal Region: Case report in a Child - Jamali, Mohammad; Ahrari, Iman; Saffarrian, Arash; Eghbal, Keyvan; Rakhsha, Abbas; Ghahramani, Sulmaz (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Introduction The pineal gland is a common location for intracranial germ cells, but dermoids are not commonly observed in this area. In the present paper, we discuss the clinical and radiological features as well as the treatment and outcome of this cyst in a 6-year- old child with a pineal dermoid cyst.Case Presentation The patient presented with chronic headache 6 months before admission in 2018. On the first admission, an enhanced lesion with a small cyst was detected in brain imaging. Magnetic resonance imaging (MRI) of the brain at follow-up (2 months after the first presentation) showed enlargement of the cyst size with compression on the adjacent structures. Radical excision of the tumor was performed after the endoscopic biopsy due to pressure exerted on the adjacent structures.Conclusion Dermoid cyst should be considered as a differential diagnosis for enhanced lesions of the pineal region.
Keywords: dermoid cyst; pineal tumor; hydrocephalus; hairy structure